SOME NEW FOSSIL REMAINS OF CHILOTHERIUM SP. FROM THE DHOK PATHAN FORMATION OF THE SIWALIKS - M. A. Khan; M. Iqbal; M. Akhtar; A. M. Khan; A. A. Majeed (Journal of Animal and Plant Sciences, 2008)
Three rhinoceros specimens from the Dhok Pathan Formation of the Middle Siwaliks of Pakistan are recovered and described in this paper. The specimens are well preserved, allowing for identification on morphological and metrical grounds as Chilotherium sp. The following investigation documents Chilotherium remains from the Dhok Pathan Formation and contributes to recent work on the Siwalik rhinoceroses.
Keywords: Rhinoceros; Dhok Pathan; Chilotherium; Middle Siwaliks